Rapid clearance of Borrelia burgdorferi from the blood circulation - Liucun Liang; Jinyong Wang; Lucas Schorter; Thu Phong Nguyen Trong; Shari Fell; Sebastian Ulrich; Reinhard K. Straubinger (Parasites & Vectors, 2020)
Abstract Background Borrelia burgdorferi is a tick-borne spirochete that causes Lyme borreliosis (LB). After an initial tick bite, it spreads from the deposition site in the dermis to distant tissues of the host. It is generally believed that this spirochete disseminates via the hematogenous route. Borrelia persica causes relapsing fever and is able to replicate in the blood stream. Currently the exact dissemination pathway of LB pathogens in the host is not known and controversially discussed. Methods In this study, we established a strict intravenous infection murine model using host-adapted spirochetes. Survival capacity and infectivity of host-adapted B. burgdorferi sensu stricto (Bbss) were compared to those of B. persica (Bp) after either intradermal (ID) injection into the dorsal skin of immunocompetent mice or strict intravenous (IV) inoculation via the jugular vein. By in vitro culture and PCR, viable spirochetes and their DNA load in peripheral blood were periodically monitored during a 49/50-day course post-injection, as well as in various tissue samples collected at day 49/50. Specific antibodies in individual plasma/serum samples were detected with serological methods. Results Regardless of ID or IV injection, DNA of Bp was present in blood samples up to day 24 post-challenge, while no Bbss was detectable in the blood circulation during the complete observation period. In contrast to the brain tropism of Bp, Bbss spirochetes were found in ear, skin, joint, bladder, and heart tissue samples of only ID-inoculated mice. All tested tissues collected from IV-challenged mice were negative for traces of Bbss. ELISA testing of serum samples showed that Bp induced gradually increasing antibody levels after ID or IV inoculation, while Bbss did so only after ID injection but not after IV inoculation. Conclusions This study allows us to draw the following conclusions: (i) Bp survives in the blood and disseminates to the host’s brain via the hematogenous route; and (ii) Bbss, in contrast, is cleared rapidly from the blood stream and is a tissue-bound spirochete.